ANALISIS STRUKTURAL PADA CERPEN LEBARAN KALI INI AKU PULANG KARYA M. AAN MANSYUR - Pardosi, Desi Andriani; Wilyanti, Liza Septa (Universitas Batanghari, 2023)
The research entitled structural analysis of the short story Lebaran Kali ini Aku Pulang by M. Aan Mansyur aims to describe the cohesiveness of the instrinsic elements contained in the story by utilizing structural analysis. The short story was studied using data collection methods, namely, reading the short story “Lebaran Kali ini Aku Pulang” reputedly and intensively, determining and studying the instrinsic elements of the short story and then describing or describing the unity between its elements. So, thet the instrinsic elements (theme, setting, characters, point of view, mandate) produce elements that are interrelated with one another.